Science education in the Eastern Caribbean: Report on primary-level development - King, Winston K.
This report on the development of primary science in the Eastern Caribbean is presented vis-a-vis the development of science education in the Caribbean generally. It discusses some of the curriculum development projects and activities that have taken place in the subregion
Special Issue: Primary education in the Commonwealth Caribbean, ed. by Donald G. Wilson
Keywords: Primary school science